Comparison of FBMC and OFDM With Adaptive Bit and Power Loading for CD-Constrained IM/DD Transmission Over 50-km SSMF - Zhang, Junwei; Tan, Heyun; Lu, Liwang; Wu, Xiong; Hong, Xiaojian; Fei, Chao; Lau, Alan Pak Tao; Lu, Chao (Journal of lightwave technology, 2024)
Filter bank multicarrier (FBMC) with offset quadrature amplitude modulation (OQAM) is a promising option for short-reach intensity modulation and direct detection (IM/DD) transmissions, as it can operate without a cyclic prefix (CP) and has lower out-of-band spectral/power leakage compared to conventional orthogonal frequency-division multiplexing (OFDM) with QAM. In this paper, we for the first time present a comprehensive comparison between high-speed IM/DD OFDM and FBMC over a chromatic dispersion (CD) constrained standard single-mode fiber (SSMF) channel. Simulation and experimental results show that FBMC exhibits better robustness against the CD-induced power fading. Compared with 0-point, 16-point, 32-point, and 64-point CP-based OFDM signals, the CP-free FBMC signal experimentally achieves significant subcarrier-SNR improvements of up to 6.5 dB, 5.6 dB, 3.7 dB, and 3.4 dB, respectively, after 50-km SSMF transmission. By using adaptive bit and power loading algorithm, 157-Gbit/s line rate and 130.3-Gbit/s net rate FBMC signal transmission over 50-km SSMF is achieved, which improves the net data rate by 26.6% compared to net-102.9-Gbit/s OFDM signal with a 32-point CP. Moreover, under the same line rate of 126.6 (131.7) Gbit/s, the adaptive bit and power loading FBMC not only increases the spectral efficiency (SE) by 6.25% (i.e., complete avoidance of inserting a CP), but also improves the receiver sensitivity by 2.9 (4.6) dB in comparison with the adaptive bit and power loading OFDM with a 32-point CP. Despite its higher computational complexity relative to OFDM, the high-speed FBMC system with superior gains shows great potential in CD-constrained IM/DD transmissions.